Investigation and Strategy Research on Dietary Nutrition Knowledge, Attitude, and Behavior of Athletes - Benyu Feng; Yu Yuan (Journal of Food Quality)
The goal of this paper is to learn more about the nutritional knowledge, attitude, and behavior of teenager trampoline athletes to improve their dietary nutritional levels as well as their sports performance. The questionnaires were designed on athletes’ diet nutrition knowledge, and the questionnaire surveys were conducted on the selected teenager trampoline athletes aged 10–17 as the survey object. Dietary nutrition knowledge, attitude, and behavior are significantly correlated with the total score P<0.05; dietary nutrition knowledge and dietary nutrition behavior are significantly correlated P<0.05; dietary nutrition attitude and dietary nutrition behavior are also significantly correlated P<0.05; dietary nutrition knowledge and dietary nutrition attitude are not strongly correlated P>0.05. The average score of dietary nutrition knowledge of teenager trampoline athletes is 6.5±1.7 (failing). The nutritional knowledge of teenager trampoline athletes is not systematic and the quality of nutrition information obtained by teenager trampoline athletes is low. The average score of dietary nutrition attitude of teenager trampoline athletes is 7.1±1.8 (good). The average score of dietary nutrition behavior is 13.4±3.1 (moderate). Teenager trampoline athletes mainly rely on coaches, relatives, and friends to obtain nutritional knowledge. Therefore, the correct eating habits need to be strengthened and their dietary nutrition behaviors need to be reasonably monitored. Suggestions will include providing relevant nutrition courses, increasing athletes’ awareness of the importance of dietary nutrition, and using professional dietitians for dietary nutrition matching and monitoring.